Santrinomics: Trends and Development of Scholarly Publications on Santri Economics in the Dimensions (2005-2024) - Maulida, Syahdatul; Rusydiana, Aam Slamet (The Economic Review of Pesantren, 2023)
Pesantren is an educational institution with the oldest style of Islamic education in Indonesia, which has been established for a long time. Currently, many pesantren have established a business and entrepreneurship-based curriculum. This study aims to review the trends and development of scientific publications related to Santri Economic, with a focus on scientific publications indexed in the Dimensions database. This research involved 246 documents, which came from 210 journal sources during the research period 2005 to 2024. The method used for analysis was Biblioshiny and R software. The results showed that scientific publications related to the concept of Santri Economic fluctuated throughout the observation period, but showed a significant upward trend in the last five years. The most frequently used keywords in these publications involve terms such as "Pesantren," "Santri," and "Pondok." In addition, this study also provides a focus on the evolution of keyword trends in Santri Economic research, illustrating the changes and developments in the focus and research approach to this topic over time.